y=ln(x^2+sinx)求导
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 01:15:54
y=ln(x^2+sinx)求导y=ln(x^2+sinx)求导y=ln(x^2+sinx)求导复合函数求导,应用链式法则y''=dy/dx=[dy/d(x^2+sinx)]*[d(x^2+sinx)/
y=ln(x^2+sinx)求导
y=ln(x^2+sinx)求导
y=ln(x^2+sinx)求导
复合函数求导,应用链式法则
y'=dy/dx=[dy/d(x^2+sinx)]*[d(x^2+sinx)/dx]=[1/(x^2+sinx)]*(2x+cosx)
故y'=(2x+cosx)/(x^2+sinx)
又由函数乘积的求导公式:(uv)
y=ln(x^2+sinx)求导
求导y=ln/sinx
求导y=ln ln ln(x^2+1)
y=ln[ln(ln x)] 求导
y=sin(lnx)+ln(sinx)求导
y=ln(2x^-1)求导
y=ln(1+x^2)求导
y=ln^2x求导
y=ln^2(1-x)求导
求导:y=[ln(1-x)]^2
求导 y=ln(tan(x/2))
求导 y=ln(-x)
y-ln((sinx)^2+(1+(sinx)^4)^1/2) 求导
求导 y=(-2x+3)sinx
y=sinx/2x 求导
求导,y=(1-x^2)/sinx
求导 y=2x*sinx
对函数y=ln[cos(arctan(sinx))]求导最后答案是-sinxcosx/(1+sinx^2)